Innovation Adoption of The Regional Government Administration Information System (SIPD) in Supporting The Planning and Budgeting Process - Penina Lambai; Djunaidi; Katriza Imania (ARISTO, 2027)
Digital transformation has positioned the Regional Government Information System (SIPD) as a strategic instrument for integrating regional planning and budgeting. However, its implementation continues to face technical challenges, limited bureaucratic capacity, and organizational adaptation. This study aims to examine the adoption of SIPD in supporting regional planning and budgeting at the Regional Development Planning, Research, and Innovation Agency (Bapperida) of East Nusa Tenggara Province through the perspective of Rogers' Innovation Adoption Theory. A qualitative phenomenological approach was employed. Data were collected through in-depth interviews, observation, and document analysis involving five purposively selected informants and analyzed using the interactive model of Miles, Huberman, and Saldaña based on Rogers' five stages of innovation adoption. The findings indicate that SIPD adoption progressed through the stages of knowledge, persuasion, decision, implementation, and confirmation. Initial knowledge was developed through formal policy communication, whereas favorable perceptions, organizational commitment, and sustained utilization evolved through practical experience, organizational learning, and institutional adaptation. Although SIPD strengthened the integration of planning and budgeting, its effectiveness remained constrained by technical challenges, data quality issues, and variations in users' capabilities. This study concludes that successful SIPD adoption depends not only on technological capability but also on organizational learning, institutional support, and continuous coordination that institutionalize digital innovation within regional planning and budgeting. Keyword: Innovation Adoption; SIPD; Regional Planning; Regional Budgeting